Falsae, suspectae vel deperditae: particularidades del corpus epigráfico ibérico de Tárraco (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper gives a global vision of the Iberian epigraphy attested in Tarraco; in particular it takes into account the false inscriptions from the 19th century, since they are one of the main difficulties in order to establish the final corpus. In the present contribution we propose that some inscriptions usually considered as genuine should be excluded from the corpus, while others, which had been rejected, could be reconsidered as authentic.  The  second  part  of  the  article  introduces  the  analysis  of  the  lost epigraphs, some of them being exclusively transmitted by manuscript tradition, and, finally, a new group of graffiti on pottery is assessed.
Keywords: Iberian Epigraphy; Iberian Language; Tarraco; Epigraphical Fakes; Epigraphical Manuscripts